Interleukin-35 and Thymoquinone nanoparticle-based intervention for liver protection against paracetamol-induced liver injury in rats - Maisa Siddiq Abduh (16381125) (2023)
Paracetamol (PAR) is a commonly used antipyretic and analgesic agent, but its excessive usage can induce liver damage and major health consequences. Interleukin-35 (IL-35) is utilized to treat immunological disorders, intestinal illness, arthritis, allergic disease, hepatitis, and cancer. Thymoquinone (THYO) is also effective against a wide range of disorders. Consequently, this study sought out to explore the ameliorative effects of IL-35 and THYO against PAR-induced hepatotoxicity in rats. Sixty male rats were separated into six groups (10 rats/group): I control (0.5 mL NaCl, 0.9%/rat via oral gavage); II (IL-35), and III (TYHO) received intraperitoneal (i.p) injection of IL-35 (200 ng/kg) or THYO (0.5 mg/kg), respectively. Group IV (PAR) received 600 mg/kg of PAR orally; V (PAR + IL-35) and VI (PAR + TYHO); rats received 600 mg/kg of PAR orally and i.p injection of IL-35 (200 ng/kg) or THYO (0.5 mg/kg), respectively. Administration of IL-35 or THYO markedly mitigated the increasing in the levels of liver parameters triggered by PAR and noticeable enhancement of antioxidant and immunological markers were observed. Additionally, IL-35 or THYO decreased TNF-α, NF-κB, IL-10, IL-6 and IFN-γ in contrast to the PAR control group. Moreover, levels of Capase-3, and cytochrome C were significantly reduced by THYO or IL35, while, levels of Bcl-2 were markedly increased. Furthermore, significant downregulation of IL1-β, TNF-α, TGF-β, and Caspas-3 genes, as well as significant upregulation of Bcl-2 and IL-10 expression were detected. In conclusion, IL-35 and THYO insulated liver from PAR toxicity by mitigating oxidative stress, tissue damage, inflammation, and apoptosis. Other Information Published in: Saudi Journal of Biological Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.sjbs.2023.103806